Measurement Motoric System of Cerebral Palsy Disability using Gross Motor Function Measure (GMFM) - Aris Rakhmadi; Ragil Ariyanto (Khazanah Informatika, 2021)
Cerebral palsy (CP) is a mobility disorder, muscle tone or posture disruption caused by brain damage that appears during brain growth, and often occurs before birth. CP has an impact on the daily activities of the suffered patient. Gross Motor Function Measure (GMFM) is a type of clinical measurement to evaluate development progress in the motoric function of CP patients. The purpose of this research is to design software to monitor and evaluate motoric parameters of CP patients. The software implements the GMFM method. The development mechanism went through the process of Software Requirements Specification (SRS). The result shows that the software helps monitor and evaluate CP patients. Software application in the field assists in evaluating the initial examination of T-1 until the final examination of T-6. Records show the enhancement dimensions of lying and rolling by 13.3%, sitting 14.8%, crawling and kneeling by 15.7%, standing by 16.5%, and walking-running-jumping 17.4%. We conclude that the application supports recording and analyzing motoric cerebral palsy data.